Association between circulating transforming growth factor-Î²1 level and polymorphisms in systemic lupus erythematosus and rheumatoid arthritis: A meta-analysis - Lee, Y. H.; Bae, S-C. (Cellular and Molecular Biology, 2017)
This study systemically reviewed evidence regarding the relationship between circulating blood transforming growth factor-Î²1 (TGF-Î²1) levels and systemic lupus erythematous (SLE) and rheumatoid arthritis (RA), and associations between TGF-Î²1 polymorphisms and susceptibility to SLE and RA. We conducted a meta-analysis on the serum/plasma TGF-Î²1 levels in SLE and RA patients and healthy controls, and the associations between TGF-Î²1 +869 T/C, +915 C/G, and -509 T/C polymorphisms and SLE or RA risk. Twenty-eight studies were considered in this meta-analysis. Circulating TGF-Î²1 levels were significantly lower in the SLE group than in controls (SMD = -1.164, 95% CI = -2.257 – -0.070, P = 0.037). Serum/plasma TGF-Î²1 levels were not significantly different between RA and control groups (SMD = 0.699, 95% CI = -0.379 – 1.717, p = 0.211). No association between TGF-Î²1 +869 T/C polymorphism and SLE was found. However, meta-analysis showed an association between the TGF-Î²1 +869 T allele and RA in all subjects (OR = 1.282, 95% CI = 1.118–1.470, P = 3.8 x 10-4). Analysis after stratification by ethnicity indicated that the T allele was significantly associated with RA in Asians and Arabs (OR = 1.429, 95% CI = 1.179–1.733, P = 2.9 x 10-4; OR = 1.352, 95% CI = 1.097–1.668, P = 0.005), but not Europeans. However, no association was found between TGF-Î²1 +915 G/C or -509 C/T polymorphisms and RA or SLE. Meta-analysis revealed a significantly lower circulating TGF-Î²1 level in SLE patients, and a significant association between TGF-Î²1 +869 T/C polymorphism and RA development.